Kedudukan Hukum Perjanjian Perikatan Jual Beli (PPJB) dalam Kegiatan Pendaftaran Peralihan Hak Atas Tanah - Rahmat Ramadhani (Iuris Studia: Jurnal Kajian Hukum, 2022)
The buying and selling process using the PPJB structure in general must be followed by an act of submission clause, in this case physical and juridical delivery (jurische levering), where in a juridical handover this is carried out by signing and making AJB before the PPAT, as regulated in a Government Regulation No. 24 of 1997 concerning Land Registration. Therefore, if there is no AJB in the buying and selling process, then it cannot be said that there has been a juridical handover, so that even though PPJB has occurred, the physical and juridical handover has not occurred. Thus, from some of these things, it can be seen that between PPJB and the sale and purchase agreement there are fundamental differences, namely related to the movement of goods or objects, where in PPJB the transfer of new goods or objects occurs in the future, while in the case of the transfer of the goods or objects in the sale and purchase agreement occur at the same time (moves instantly from the seller to the buyer). In the concept of buying and selling land and/or buildings, the transfer of land rights only occurs after the signing of the AJB in the presence of the authorized official, namely PPAT. This research is descriptive analytical with the approach used is normative juridical. The data collected is then processed and analyzed qualitatively, using an inductive method to draw a conclusion